Barriers of community capacity building in types of tourism activities - Aref, Fariborz; Gill, Sarjit S. (Marsland Press, 2010)
This paper investigates barriers of community capacity building in tourism development base on types of tourism activities. This study was run in local communities of Shiraz, Iran. Questionnaire was used to collect data from community leaders. The focus group discussion also performed to collection data from community residents who were engaged in tourism activates. One way Anova was used to examine the difference barriers of community capacity base on types of tourism activities. According to the survey, results showed barriers of community capacity building in tourism development in handicraft activities higher than other types of tourism activity.